An Industrial Heritage Case Study in Ayvalik: Ertem Olive Oil Factory - GOZDE YILDIZ; NERIMAN SAHIN GUCHAN (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
Ayvalik is a pioneer settlement in the West Anatolia with an olive-based industry since its establishment. However, due to fast technological developments and changes in production systems, there is a large stock of derelict industrial buildings within the city centre. In addition, a few of them are restored under poor conditions as a result of financial profits. This situation puts Ayvalik’s olive industrial heritage which constitutes the identity of the town at critical risk of extinction. Ertem Olive Oil Factory is one of the industrial heritage buildings in Ayvalik dating back to 1910 which is a typical well preserved-medium scale 19th-century olive oil factory including both olive oil and soap productions. The aim of this paper is to discuss a conservation approach for the industrial settlement of Ayvalik by assessing the factory and its close environment through values, problems and potentials. The paper thus begins with a brief history of Ayvalik and the effects of industrialization on the city. It continues with theoretical principles of adaptive re-use through contemporary literature and general evaluation of adaptive re-use examples in Ayvalik according to these principles. The third part focuses on the general characteristics of Ertem Olive Oil Factory and its close environment. The final part discusses the conservation approach for the adaptive re-use through values, problems and potentials of the building and Ayvalik.